The Application of Affine/Interval Algebra to Determine the Time of Concrete Cover Damage in Reinforced Concrete Due to Corrosion - Krykowski, Tomasz (Computer Assisted Methods in Engineering and Science; Vol 27 No 4 (2020), 2020)
This paper presents the application of affine numbers to determine the time of concrete cover cracking in reinforced concrete elements from the initiation of the reinforcement corrosion. This issue is crucial for evaluating sustainability and durability of reinforced concrete structures. The proposed general approach has been used to forecast displacements and crack propagation versus time in reinforced concrete elements subjected to corrosion tests. The affine approach equations describing changes caused by the formation of corrosion products are defined and the corresponding tensor of the volumetric strain rate is formulated. The time of cover cracking has been analysed using the Finite Element Method (FEM) and the Monte Carlo (MC) method to verify the correctness of calculations.